Analisis Pekerjaan Terhadap Kinerja Karyawan - Anisa Ayu Ramadina; Alexandra y.n Mbakung; Sella Mariska; Chytaradhea Anindhita; Yuliana Aurelia Ludu (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the effect of job analysis on employee performance. The method used is a literature review, which involves collecting and analyzing data from five recent journals related to this theme. The research results show that clear and systematic job analysis contributes significantly to improving employee performance through a better understanding of duties and responsibilities.